"I must have taken a fake TOEFL!": Rethinking Linguistically Responsive Instruction Through the Eyes of Chinese International Freshmen. Issue 4 (1st November 2021) - Zhang‐Wu, Qianqian; Brisk, Maria Estela
Abstract: Although being able to meet the TOEFL requirement for college admission, Chinese international students often encounter linguistic challenges during their initial college experiences. Understanding such challenges set the foundation for implementing Linguistically Responsive Instruction (LRI) in higher education. Although well studied in K‐12 settings, LRI remains under‐researched in higher education. Furthermore, often designed based upon teachers' experiences, little research examines LRI through the lenses of students. In this exploratory qualitative study, we adopt a student‐centered approach to (re)imagine LRI in higher education based on the first‐semester experiences of 12 Chinese international freshmen. Drawing upon semi‐structured interviews, bilingual language logs, and WeChat observation, our study explores (1) What were Chinese international freshmen's language and academic experiences during the first half of the semester? (2) What were their experiences throughout the rest of the semester and how do these experiences inform an LRI model to support multilingual students in higher education? The findings address participants' challenges, coping strategies, and interactions within the university community and highlight the within‐group variabilities among Chinese international students. This study emphasizes the need to understand multilingual international students' experiences beyond their TOEFL scores, which paves way for rethinking LRI in higher education through the lenses of students. Abstract :